The Effect of Vitamin D Supplementation on Prostate Cancer: A Systematic Review and Meta-Analysis of Clinical Trials - Shahvazi, Simin; Soltani, Sepideh; Ahmadi, Seyed Mehdi; de Souza, Russell J.; Salehi-Abargouei, Amin (Hormone and Metabolic Research, 2019)
Vitamin D has received attention for its potential to disrupt cancer processes. However, its effect in the treatment of prostate cancer is controversial. This study aimed to assess the effect of vitamin D supplementation on patients with prostate cancer. In the present study, PubMed, Scopus, ISI Web of Science, and Google Scholar were searched up to September 2017 for trials that evaluated the effect of vitamin D supplementation on prostate specific antigen (PSA) response, mortality, and its possible side effects in participants with prostate cancer. The DerSimonian and Laird inverse-weighted random-effects model was used to pool the effect estimates. Twenty-two studies (16 before-after and 6 randomized controlled trials) were found and included in the meta-analysis. The analysis of controlled clinical trials revealed that PSA change from baseline [weighted mean difference (WMD)=–1.66 ng/ml, 95% CI: –0.69, 0.36, p=0.543)], PSA response proportion (RP=1.18, 95% CI: 0.97, 1.45, p=0.104) and mortality rate (risk ratio (RR)=1.05, 95% CI: 0.81–1.36; p=0.713) were not significantly different between vitamin D supplementation and placebo groups. Single arm trials revealed that vitamin D supplementation had a modest effect on PSA response proportion: 19% of those enrolled had at least a 50% reduction in PSA by the end of treatment (95% CI: 7% to 31%; p=0.002). Although before-after studies showed that vitamin D increases the PSA response proportion, it does not seem that patients with prostate cancer benefit from high dose vitamin D supplementation and it should not be recommended for the treatment.
Keywords: vitamin D; prostatic neoplasms; PSA response; mortality; systematic review; meta-analysis